Treatment of chronic ulcers - Busch, Ch.; Aschermann, I.; Mnich, Ch.D. (Phlebologie, 2017)
Chronic ulcers (CUs) are a major cause of morbidity and mortality with increasing prevalence, in part due to the ageing population, and an increase of risk factors such as diabetes and obesity. CUs are caused by numerous diseases including venous dysfunction, diabetes mellitus, infections, peripheral neuropathy, pressure, and atherosclerosis. The current standard therapy for CUs includes compression, surgical débridement, infection control, and adequate wound dressings. As a high percentage of CUs do not adequately heal or quickly relapse with standard treatments, additional therapeutic approaches are pursued, termed “advanced wound care therapies”. Here, an overview on commonly applied therapies lacking significant evidence for wound healing is reviewed, followed by therapies with significant evidence supporting the routine use in the treatment of CUs, and a short outlook in a possible future wound treatment landscape.To give a résumé, the presented literature reveals that most of the commonly applied topical and advanced ulcer treatments largely lack solid scientific evidence for the induction or acceleration of wound healing. Surprisingly only “classical” treatments such as wound cleansing, débridement and compression have significant evidence. Novel approaches such as bilayered skin reconstructs, cell suspensions or extracorporal shock waves seem promising. Considering the increasing number of ulcer patients, there is a strong need for further basic research to fully understand all factors involved in wound development and healing of the various ulcer pathophysiologies, and the urgent need for prospective clinical trials comparing the various treatment options.
Keywords: Ulcer; wound healing; wound dressing; therapy